Active support of underground and open pit mining excavations using resin mortar in anchor bolts and tendons - Ortiz Sánchez, Oswaldo (2003)
The anchor bolt or tendon is an effective, simple and quick installation and lower cost support device than any of the known support methods. There is a wide variety of bolts and tendons to fix the rock, ranging from wooden bolts to iron pipe bolts and smooth and corrugated steel rods with anchors that are generally of two kinds: point and longitudinal. The most widespread at present is the longitudinal anchor, of which the cement grout anchor is used more for its ease of application and low cost. The cement grout, however, has deficiencies for its application in anchorage due to its low resistance to tension and shear, volumetric contraction when setting, low adherence capacity, long setting period, low resistance to corrosion, humidity , to weathering and vibrations. The alternative is resin, but its high cost has practically eliminated its use as an anchor for bolts and tendons, especially in the mining industry. The solution proposed in this study is the use of a resin mortar consisting of gravel of a certain grain size and expansive resin in a ratio of 4 to 1, which would allow the return of the resin as a bolt anchor both in underground mining as in the surface and in countless other land consolidation applications in the field of civil engineering. Laboratory tests carried out show that resin mortar has higher levels of adhesion to rock than cement grout. Additionally, the setting is fast, it has great resistance to acid or alkaline corrosion, it supports humidity and high vibrations. For the application of gravel, a pneumatic injector has been designed whose characteristic is to use the available air from the mining operation or from any compressor. The installation of the bolt or tendon has the following sequence: 1st drilling of the drill to the required depth and diameter, 2nd installation of the bolt or tendon, 3rd injection of gravel in the empty spaces of the drill, 4th injection of resin (two components), by means of a pump that works at variable pressures up to 200 bar, this being adjustable according to the requirements. The system is applicable to the roof, walls or floor of the excavation and the application time is not significantly longer than that used in the installation of the other types of bolts (5 to 7 minutes per bolt).